Increasing Knowledge through Counseling Activities of HIV/AIDS at Yakbado SMTK Dogiyai District - Isak Waine; Joko Prasetyo (Journal of Community Engagement in Health, 2024)
Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) is a health problem in the world, including Indonesia. The number of HIV/AIDS cases continues to increase from year to year. HIV/AIDS is a deadly disease for which no cure has been found needed innovation to cure HIV/AIDS sufferers. Therefore, it is necessary to carry out counseling to prevent an increase in HIV/AIDS sufferers in public. Counseling activities about HIV/AIDS were carried out on August 25 2023 at SMTK Yakbado, Dogiyai Regency, using counseling and questionnaires in the form of Pre-Test and Post Test tested statistically. The results of statistical tests show that there was an increase in knowledge before and after counseling about HIV/AIDS from the results (pretest 6.30% and posttest 7,88%) from 28 Students with 10 questions.